Assessment of Groundwater Suitability for Irrigation in Dadin-Kowa, Yamaltu Deba LGA, Gombe State, Nigeria - Sule, S.; Abashiya, M.; Didams, G. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
In semi-arid regions, the quality of irrigation water and soil salinity were the main factors limiting agricultural yield in irrigation schemes. The increasing salinity of groundwater used in hot, dry regions with limited rainfall limits the variety of crops that can be produced. Therefore, it is crucial to ascertain the quality of the irrigation water. This study examined the physicochemical composition of the groundwater at the Dadin-kowa irrigation site and determined if it was suitable for irrigation. Using 1.5 liter sterilized bottles, four (4) water samples were taken from boreholes. The samples were then tested using conventional protocols for key physicochemical quality parameters, such as pH, ECw, TDS, Ca++, Mg++, Na+, HCO-3, CI-, SO-4, NO3-, K+, SAR, and SSP. The Food and Agriculture Organization (FAO) standard recommendations were followed in the quality evaluation of each parameter of the water samples for irrigation suitability. The findings of the study revealed that most of the tested parameters, including CI-(385.8 ± 104.3 mg/l), K+(5.5 ± 2.9 mg/l), Na+(70.2 ± 26.8 mg/l), Mg++(24.2 ± 5.05 mg/l), Ca++(32.0 ± 2.83 mg/l), and Na+(70.2 ± 26.8 mg/l) were found to be higher than the FAO threshold level for irrigation. This led to the conclusion that there are now a lot of risks connected to using groundwater for irrigation in the research region. Therefore, stress the necessity of using the area’s water quality as a reference for suitable management methods in irrigated agriculture in order to preserve the soil’s current productivity and reap the benefits of a high crop yield.